On path related graphs with constant metric dimension - Ali M.; Rahim M.T.; Ali G. (Utilitas Mathematica, 2012)
Let G is a connected graph. A set of vertices W resolves a graph G, if every vertex is uniquely determined by its coordinate of distances to the vertices in W. The minimum cardinality of resolving set G is called the metric dimension of G. In this paper, we show that the graphs P 2 n, P 3 n, M(P n) and T(P n) have constant metric dimension.